Pemanfaatan Media Podcast sebagai Sarana Pembelajaran untuk Meningkatkan Kemampuan Berbicara Siswa Kelas VIII Sekolah Menengah Pertama Negeri 23 Medan Tahun Pelajaran 2024–2025 - Wahyuni, Miranda Sri; Pulungan, Rosmilan (Jurnal Bahastra, 2025)
This study aims to examine the utilization of podcast media as an instructional tool to enhance the speaking skills of eighth-grade students at Public Junior High School 23 Medan during the 2024–2025 academic year. Speaking competence is a crucial aspect of language learning, as it directly relates to students’ ability to express ideas, thoughts, and information orally. However, many students still struggle with speaking due to limited vocabulary, insufficient practice, and monotonous teaching methods. The use of podcasts in the learning process offers an innovative, engaging, and easily accessible medium that encourages autonomous and collaborative learning. Through podcasts, students can listen to appropriate speech models, practice pronunciation and intonation, and expand their vocabulary. This research employed a classroom action research (CAR) design to observe improvements across learning cycles. The findings reveal that consistent use of podcast media significantly improved students’ speaking performance, as reflected in the increased average scores at each stage. Therefore, podcast-based learning proves to be an effective and relevant medium for fostering speaking proficiency among junior high school students.